Stages of Professional Teacher Development and Teacher Professional and Career Development Policy - Maspuroh Maspuroh; Muhammad Makbul Fauzan; M. Naufal Rafitaqiyuddin; Rafli Raisa Dahlan (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Strengthening the professionalism of educators is a crucial element in improving the quality of education. This paper reviews the process of professional teacher development, the steps taken, and policies related to teacher career and professional development. This study uses a qualitative descriptive method with a literature study approach to analyze existing teacher development policies and models in Indonesia. The results of the study indicate that professional teacher development consists of several stages, namely the initial education stage, induction, continuing professional development, and career levels supported by government policies. The teacher development process involves various training programs, certification, and performance-based evaluation systems. The policy for teacher professional development in Indonesia still faces several challenges, such as equal access to training and performance evaluation that has not been maximized. This article recommends improvements in teacher professional development policies in order to improve the quality of education sustainably.